Prevalence and risk factors of low back pain in middle-aged and older adult in China: a cross-sectional study - Xue Jiang; Rui Wang; Yi-Wen Bai; Le Tang; Wen-Yuan Xing; Nan Chen; Xue-Qiang Wang (Archives of Public Health)
Abstract Background The study aimed to determine the prevalence of low back pain (LBP) and risk factors among people aged 45 years and above in Mainland China. Methods This cross-sectional analysis was based on data from 15,743 individuals obtained from the China Health and Retirement Longitudinal Study in 2018. We sampled people aged 45 years and above, representing the national population, with a response rate of 83.8%. Weighted logistic regression analyses were utilized to ascertain factors linked to the prevalence of LBP. Results The overall prevalence of LBP was 38.5% (37.7–39.2). Female (odds ratio [OR] 2.24 [1.78–2.81], higher education level (OR 1.24 [1.04–1.49]), poorer health status (OR 2.96 [2.44–3.60]), more chronic diseases (OR 1.32 [1.09–1.61]), insufficient sleep (OR 1.45 [1.26–1.67]), alcohol consumption (OR 1.25 [1.04–1.50]), depression (OR 1.39 [1.22–1.59]), and engagement in agricultural work (OR 1.50 [1.32–1.70]) exhibited significant associations with LBP. Conclusion Among Chinese adults aged 45 years and above, the prevalence of LBP was 38.5%. Significant risk factors for LBP comprised poor health status, a greater number of chronic diseases, poor sleep, alcohol consumption, depression, and employment in the agricultural work. Trial registration Not applicable.